Methodology of Teaching Physical Culture and Sports - Sotivoldiev Kadir Rakhimovich (Research Parks Publishing LLC, 2021)
The fact that sport is a guarantee of health and strengthening of certain parts of the body through various exercises, on this basis for ensuring human health, is emphasized in the medical writings of Abu Ali ibn Sina. Our great ancestor recommended different exercises for the development of different parts of the body, probably hence the variety and variety of sports